Perbedaan Pengetahuan Dan Sikap Sebelum Dan Sesudah Pendidikan Kesehatan Tentang Stroke Pada Penderita Hipertensi - Linda Adriani; Sarilina Putri (STIKes Darussalam Lhokseumawe, 2019)
Hypertension can occur due to an unhealthy lifestyle, so that it can cause various kinds of complications. So that hypertension sufferers can reduce the occurrence of stroke, it requires good knowledge and awareness about hypertension care and correct stroke prevention. One effort to increase the level of client knowledge about the dangers of an illness by providing health education. Health education is an independent nursing intervention to assist clients in overcoming their health problems through learning activities, thereby increasing knowledge and behavior to prevent illness and improve health. This study aims to identify the Differences in Knowledge and Attitudes Before and After Health Education About Stroke in Patients with Hypertension in Singah Mulo Health Center, Bener Meriah Regency. This study uses a comparative test or comparison test. The sampling technique is by taking a total population of 50 people with inclusion criteria. Data collection tools such as questionnaires and primary and secondary data. The results showed there were differences in knowledge and attitudes before and after health education. The average value (mean) of knowledge before health education was 13.30 and after health education was 13.90 with a difference in the mean value of 0.60. The average (mean) attitude before health education was 70.64 and after health education was 72.68 with a mean difference of 2.04.